Desain dan Pemanfaatan Media Pembelajaran Flash Card dengan Canva untuk Disabilitas - Rosihan Ari Yuana; Cucuk Wawan Budiyanto; Nurcahya Pradana Taufik Prakisya; Puspanda Hatta; Yusfia Hafid Aristyagama; Febri Liantoni (DEDIKASI: Community Service Reports, 2024)
Students with disabilities require suitable educational materials. Hence, one of the essential skills that a teacher must possess is the ability to provide suitable instructional materials for students. A workshop was organized by this community service activity at SLB YPCM Boyolali, focusing on creating educational media for instructors using Canva. The training instructs teachers on how to design flashcards specifically tailored for students with disabilities to facilitate their learning process. The advantage of this activity is the enhanced proficiency of SLB YPCM Boyolali teachers in creating digital educational materials. Another advantage is assessing instructor perspectives when employing digital media for educational purposes. The school will provide students with exceptional needs the opportunity to develop the skill of product branding using the processed foods they create. The post-workshop evaluation results indicate that this activity is highly successful and positively influences participants. Evidence demonstrates that 90% of participants can generate flashcard learning media products using Canva. The participants had a favorable opinion of Canva due to its user-friendly interface and comprehensive range of functions, despite most participants having limited computer proficiency. The session presented was met with a high level of satisfaction from most attendees.